NETRALISME ANTAR ETNIK DALAM INTERAKSI SOSIAL PASAR TRADISIONAL DI PASAR TUNTUNGAN, MEDAN - Nuriza Dora; Saripah Aini Simbolon; Cahaya Permata Sari (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study aims to examine the dynamics of inter-ethnic neutrality that is formed and maintained in social interactions at Tuntungan Market, Medan. This market is one of the traditional markets inhabited by communities with various ethnic backgrounds such as Batak, Karo, and Javanese, so that this market becomes a social forum that reflects unity amidst differences. The method used in this study is qualitative with a descriptive approach. Data collection techniques through interviews, observations, and documentation. The findings of the study indicate that inter-ethnic interactions occur in a neutral and harmonious atmosphere, which can be seen from the use of Indonesian as the main language of communication, a professional attitude in buying and selling transactions, and the absence of ethnic-based conflicts. The attitude of helping each other, social awareness, and common economic interests are the main factors that give birth to this neutrality. Neutrality in the market does not eliminate each other's cultural identities, but builds functional cooperation and mutual respect to create a peaceful and productive social life. The results of the study show that social interactions in the Tuntungan traditional market are dominated by the practice of neutralism, namely the attitude of mutual acceptance and setting aside ethnic differences for the sake of economic and social interests. Where this neutralism is formed through economic cooperation, cultural tolerance and the use of market language as a unifying tool.